Determinan Kejadian Morbiditas Lansia di Pedesaan di Provinsi Sulawesi Tenggara Tahun 2020 - Risma Dwi Lestari; Titik Harsanti (Seminar Nasional Official Statistics, 2022)
The morbidity rate can be used to see the health quality of an area. In 2020 Southeast Sulawesi experienced an increase in morbidity and this figure was dominated by the elderly population, especially in rural areas. Therefore, this study aims to analyze the incidence of elderly morbidity in rural Southeast Sulawesi using Susenas KOR 2020 data and binary logistic regression methods. The results of data processing showed that family size, ownership of health insurance, smoking status, age, education level, and working status had a significant effect on the incidence of rural elderly morbidity. Rural elderly in small families, have health insurance, do not smoke, are 70 years old and over, do not attend school or do not finish elementary school, and do not work have a greater tendency to experience morbidity. Therefore, special attention is needed regarding the health status of the elderly, especially for the elderly who are over 70 years old and do not have a job.